ORGANISMOS INTERNACIONAIS E GRANDES EVENTOS ESPORTIVOS: novas dinâmicas da dominação burguesa para o século XXI - Marcelo Paula de Melo (Motrivivência, 2010)
The aim of this paper is to presentsome elements of consideration ofthe relationship between the politicalrole of international organizations ofcapital (World Bank, UN / UNESCO)and the area of physical educationand sports. More specifically wewill bring some documents of theseorganic intellectuals of the bourgeoisworld that analyze the major sportingevents. With it, you can uncoversome educational elements of bourgeoisrule in our time and its impacton the field of physical educationand sport.